Fylgikvillar við keisaraskurði - Heiðdís Valgeirsdóttir; Hildur Harðardóttir; Ragnheiður I. Bjarnadóttir (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) OBJECTIVE: The objective of the study was to determine the rate of complications which accompany cesarean sections at Landspitali University Hospital (LSH). MATERIAL AND METHODS: All deliveries by cesarean section from July 1st 2001 to December 31st 2002 were examined in a retrospective manner. Information was collected from maternity records regarding the operation and its complications if they occurred, during or following the operation. RESULTS: During this period 761 women delivered by cesarean section at LSH. The overall complication rate was 35,5%. The most common complications were; blood loss > or =1000 ml (16.5%), post operative fever (12.2%), extension from the uterine incision (7.2%) and need for blood transfusion (4.3%). Blood transfusion was most common in women undergoing cesarean section after attempted instrumental vaginal delivery (20%). Fever and extension from the uterine incision were most common in women undergoing cesarean section after full cervical dilation without attempt of instrumental delivery (19,4%). These complications were least likely to occur if the patient underwent an elective cesarean section. CONCLUSION: Complications following cesarean section are common, especially if labor is advanced. Each indication for an operative delivery should be carefully weighed and the patient informed accordingly. Inngangur: Tilgangur rannsóknarinnar var að kanna tíðni fylgikvilla við keisaraskurði á Landspítala og bera saman við tíðni erlendis. Skoðaðir voru fylgikvillar sem upp komu í aðgerð eða á fyrstu dögum eftir fæðingu. Efniviður og aðferðir: Þýði rannsóknarinnar var konur sem fæddu með keisaraskurði á Landspítala frá 1. júlí 2001 til 31. desember 2002. Upplýsingum um aðgerð og feril sjúklings í kjölfarið var safnað á afturvirkan hátt úr mæðraskrá og sjúkraskrám spítalans. Niðurstöður: Á tímabilinu var framkvæmdur 761 keisaraskurður. Heildartíðni fylgikvilla var 35,5%. ...